The Freedom of Contract - Ali, Moh.; Prakoso, Bhim (Indonesian Journal of Law and Society, 2023)
The presence of free trade zone and the increase in cross-border trade, have led to a significant increase in transnational legal relations. As a result, international contracts have become more common, and the principles of freedom of contract, including the freedom to choose the law and forum, have become increasingly important. Freedom of contract is a very universal principle. Almost all countries in the world recognize it as a very fundamental principle in contracts, even in international business contracts. This principle recognizes that contracts made by the parties act as laws for the parties that compile them. However, there is still lacking consistency among Indonesian judges in their interpretation of the choice of law and forum in international contracts. This study examined the raison d’ etre of different views and decisions of Indonesian judges in interpreting the choice of law and the choice of forum, and its implication to the principle of legal certainty in international business disputes. Through the normative legal research which elaborated with a case study, this research finds that The views of some Indonesian court judges deviate from the principle of freedom of contract where the law that has been chosen by the parties is based on considerations of the principle of effectiveness besides focusing on the nature of the case handled so that the decision can be executable. The court may need to balance the principle of freedom of contract with other important considerations in order to arrive at a fair decision. This is why it is important for judges to have a clear understanding of both the principles of freedom of contract and the practical implications of their decisions in order to promote legal certainty in international business transactions.